Temperature Differentially Affects Gene Expression in Antarctic Thraustochytrid Oblongichytrium sp. RT2316-13 - Paris Paredes; Giovanni Larama; Liset Flores; Allison Leyton; Carmen Gloria Ili; Juan A. Asenjo; Yusuf Chisti; Carolina Shene (Marine Drugs, 2020)
Oblongichytrium RT2316-13 synthesizes lipids rich in eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). The content of these fatty acids in the total lipids depended on growth temperature. Sequencing technology was used in this work to examine the thraustochytrid’s response to a decrease in growth temperature from 15 °C to 5 °C. Around 4% (2944) of the genes were differentially expressed (DE) and only a few of the DE genes (533 upregulated; 206 downregulated) had significant matches to those in the SwissProt database. Most of the annotated DE genes were related to cell membrane composition (fatty acids, sterols, phosphatidylinositol), the membrane enzymes linked to cell energetics, and membrane structure (cytoskeletal proteins and enzymes). In RT2316-13, the synthesis of long-chain polyunsaturated fatty acids occurred through ω3- and ω6-pathways. Enzymes of the alternative pathways (Δ8-desaturase and Δ9-elongase) were also expressed. The upregulation of the genes coding for a Δ5-desaturase and a Δ5-elongase involved in the synthesis of EPA and DHA, explained the enrichment of total lipid with these two long-chain fatty acids at the low temperature. This molecular response has the potential to be used for producing microbial lipids with a fatty acids profile similar to that of fish oils.